Design And Analysis Of A Fast Transient Voltage Regulator With All Ceramic Output Capacitors For Mobile Microprocessors - Lee , Chun Heng (2015)

(untitled)
The need to have fast transient response of the voltage regulator is driven by the increasing current slew rate of the mobile microprocessor. Hence, optimizing the switching frequency of the voltage regulator becomes an important step to achieve a balance between preserving the efficiency of the voltage regulator and improving the transient response. Besides, output capacitor solution with multilayer ceramic capacitor has also become more popular due to its small size and cheap cost. Over the years, even though the topology of the buck converter remains unchanged, there are plenty of innovations and breakthroughs in the power stage of the voltage regulator and controller technology. In addition, output impedance oriented design and adaptive voltage positioning (AVP) feature are also introduced to address the transient requirements. Apart from improving the dynamic response of the voltage regulator, many research works also focus on improving the efficiency of the voltage regulator, especially for battery-powered systems. A fast transient voltage regulator with all ceramic output capacitors for mobile microprocessor is proposed in this study. The outcome of the study shows that the voltage regulator designed is stable with the proposed type and number of multilayer ceramic capacitors. More importantly, the actual transient results correlate well with the simulation results where minimal transient droop and overshoot are observed with a dynamic current load step with a slew rate of 10.5A per 1 μs. In conclusion, a fast transient voltage regulator with all ceramic output capacitors is designed and analyzed which proven to have better transient performance compared to the original design on the test board.